Early neuronal loss and axonal/presynaptic damage is associated with accelerated amyloid-β accumulation in AβPP/PS1 Alzheimer's disease mice subiculum. - Trujillo-Estrada, Laura Isabel; Dávila-Cansino, José Carlos; Sánchez-Mejías, Elisabeth; Sánchez-Varo, Raquel María; Gómez-Arboledas, Ángela; Vizuete, Marisa; Vitorica Ferrández, Javier; Gutiérrez-Pérez, Antonia (IOS Press, 2014)
The progressive cognitive decline leading to dementia in Alzheimer’s disease (AD) patients is the consequence of a severe loss of synapses and neurons affecting particular cell subpopulations in selected brain areas, with the subiculum being one of the earliest regions displaying severe atrophy and pathology. The lack of significant neuronal loss in most AD models is, in fact, the major shortcoming for the preclinical evaluation of drugs that could have greater potential in patients to alleviate or prevent this disease. In this study, using immunohistochemical and stereological approaches, we have analyzed the histopathological events in the subiculum of APP751SwedLondon/PS1M146L mice, a transgenic model that displays neuronal vulnerability at early ages in hippocampus and entorhinal cortex. Our results indicate that the subiculum is the earliest affected region in the hippocampus, showing a selective early loss of both principal neurons (28%) and SOM-positive interneurons (69%). In addition, our data demonstrate the existence of an early axonal and synaptic pathology, which may represent the beginning of the synapticdisruption and loss. These neurodegenerative processes occur in parallel, and closely related, with the onset and accelerated progression of the extracellular amyloid-beta deposition, thus suggesting plaques as major contributors of neuronal/axonal damage. Data reported here indicate that this AD model displays a selective AD-like neurodegenerative phenotype in highly vulnerable regions, including the subiculum, and therefore can be a very useful model for testing the therapeutic ability of potential compounds to protect neurons and ameliorate disease symptoms.
Keywords: Alzheimer, Enfermedad de - Modelos animales; Sistema nervioso - Degeneración; Hipocampo (Cerebro); Alzheimer’s disease; Amyloid beta plaques; Hippocampus; Transgenic mice; Axonal damage; Neuronal loss; Subiculum